2020
DOI: 10.1111/jonm.13133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organisational restructuring of hospitals on nurses

Abstract: In the last quarter century, there have been worldwide changes in the way public institutions operate and are organised. These changes have impacted government staffing and employment strategies, and personnel promotion and evaluation approaches. Health care policies and the governments' roles and responsibilities in health care were transformed in the process, as much as the changes in the understanding of the public and the staffing system were reflected in the field of health care (Özkal Sayan & Küçük, 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Galván Mendoza, Oscar Alienación laboral, violencia En este sentido, dado los hallazgos encontrados en el presente estudio, tal cual se predijo, la variable violencia de género impacta de manera positiva y estadísticamente significativa a la alienación laboral, lo cual coincide con lo establecido a priori dentro de la evidencia científica disponible, por autores como Bilgin y Buzlu (2006); Settles et al (2012); y, London et al (2012). De forma semejante, en concordancia con lo establecido dentro de la literatura especializada, la alienación laboral impacta de manera negativa y estadísticamente significativa a la satisfacción laboral (Ertekin y Özmen, 2017;Galván-Mendoza y Esquinca-Moreno, 2019;Kumral et al (2020). Adicionalmente, se detectó que la violencia de género posee un efecto predictivo considerable sobre la variable alienación laboral.…”
Section: Figura I: Modelo Estructuralunclassified
“…Galván Mendoza, Oscar Alienación laboral, violencia En este sentido, dado los hallazgos encontrados en el presente estudio, tal cual se predijo, la variable violencia de género impacta de manera positiva y estadísticamente significativa a la alienación laboral, lo cual coincide con lo establecido a priori dentro de la evidencia científica disponible, por autores como Bilgin y Buzlu (2006); Settles et al (2012); y, London et al (2012). De forma semejante, en concordancia con lo establecido dentro de la literatura especializada, la alienación laboral impacta de manera negativa y estadísticamente significativa a la satisfacción laboral (Ertekin y Özmen, 2017;Galván-Mendoza y Esquinca-Moreno, 2019;Kumral et al (2020). Adicionalmente, se detectó que la violencia de género posee un efecto predictivo considerable sobre la variable alienación laboral.…”
Section: Figura I: Modelo Estructuralunclassified
“…Previous research confirmed that nurses' work alienation influenced their work effort, attitude toward organizational change, organizational commitment, and job performance. 5,6 Work alienation is an important indicator reflecting the negative psychological state of employees and can predict negative behavior, willingness to leave the workplace, or actual turnover of employees to some extent. 5 Considering the fact that nurses have a high turnover rate and there is a shortage of nursing staff, 7,8 it is necessary to identify predictors of work alienation and find effective interventions.…”
mentioning
confidence: 99%